Implementasi Pemberian Reward dan Punishment dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 1 Natar Kabupaten Lampung Selatan - Junaida; Imam Syafe’i; Sovia Mas Ayu (CV. Creative Tugu Pena, 2024)
The objectives of the study are (1) To analyze the objectives of Reward and Punishment in Islamic Religious Education Learning at SMA Negeri 1 Natar, South Lampung Regency. (2) To analyze the forms of Reward and Punishment in Islamic Religious Education Learning at SMA Negeri 1 Natar, South Lampung Regency. (3) To analyze the steps of Reward and Punishment in Islamic Religious Education Learning at SMA Negeri 1 Natar, South Lampung Regency. This type of research is a type of qualitative research with a qualitative descriptive approach. The population in this study were all class X students at SMA Negeri 1 Natar, South Lampung Regency in the 2023-2024 academic year, totaling 40 students. Data collection techniques in this study used observation, interviews and documentation. The data obtained were analyzed using data analysis techniques in the form of qualitative analysis with source triangulation and method triangulation techniques. The conclusion of this study is (1) The purpose of giving rewards and punishments is to increase students' learning motivation during Islamic Religious Education learning, (2) The forms of rewards and punishments applied: thumbs up, activeness scores, attention, praise, prizes. While the forms of punishment are: verbal warnings, cleaning up trash in the classroom, giving assignments in class, and asking questions, (3) Steps for Giving Rewards and Punishments: planning the implementation of rewards and punishments, the teacher carries out the planning that has been agreed upon in class, the teacher reviews the lessons that have been previously studied, the teacher begins to enter the core of the lesson, the teacher explains the implementation of rewards and punishments that will be given to students depending on how the students behave. If students follow the lesson well and obey class rules, the teacher will give rewards in the form of extra marks and prizes.